PROFESIONALISME GURU MENURUT PERSFEKTIF AL QURAN DAN AL HADIST - Yumawan, Restia Lasri; Anwar, Cecep (Prodi Ilmu Al-Qur'an dan Tafsir, 2022)
This study aims to examine the meaning of teacher professionalism from the perspective of thal Quran and al Hadist. The method used in this research is a qualitative research with a literature study approach. The data used in this study are in the form of document data, both from al Quran, al Hadist, textbooks, scientific journals, and other relevant document sources. In terms of this literature study approach, researchers look for literature or library data in the form of teacher professionalism according to the perspective of al Quran and al Hadist. The results show that professional work must be matched with expertise. Teacher professionalism in the Qur'an shows that the teacher must have a democratic nature, be patient and be gentle in carrying out his noble duties, forgive and be consistent with his duties and responsibilities, be able to work together (cooperatively) and be compassionate both in action and in the form of prayer. In addition, professional teachers are also required to understand the student’s psychology, imitate the character of the Prophet Muhammad in the learning process and master knowledge in their fields. The results of this study are expected to be used as a reference for the teacher to improve their professionalism refers to al Quran and al Hadist, that implicated the quality of education and the educational goals.